Nonlinear PI Control With Adaptive Interaction Algorithm For Multivariable Wastewater Treatment Process - Samsudin, Sharatul Izah; Rahmat, Mohd Fuaad; Abd Wahab, Norhaliza (Hindawi Publishing Corporation, 2014)
The wastewater treatment plant (WWTP) is highly known with the nonlinearity of the control parameters,thus it is difficult to be controlled.In this paper,the enhancement of nonlinear PI controller (ENon-PI) to compensate the nonlinearity of the activated sludge WWTP is proposed.The ENon-PI controller is designed by cascading a sector-bounded nonlinear gain to linear PI controller.The rate variation of the nonlinear gain k n is automatically updated based on adaptive interaction algorithm.Initiative to simplify the ENon-PI control structure by adapting k n has been proved by significant improvement under various dynamic influents.More than 30% of integral square error and 14% of integral absolute error are reduced compared to benchmark PI for DO control and nitrate in nitrogen removal control.Better average effluent qualities, less number of effluent violations, and lower aeration energy consumption resulted.